2007
DOI: 10.1124/dmd.106.014068
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Plasma Concentrations of Antiangiogenic Agent TSU-68 ((Z)-5-[(1,2-Dihydro-2-oxo-3H-indol-3-ylidene)methyl]-2,4-dimethyl-1H-pyrrole-3-propanoic acid) during Oral Administration Twice a Day to Rats

Abstract: ABSTRACT:TSU-68 ((Z)-5-[(1,2-dihydro-2-oxo-3H-indol-3-ylidene)methyl]-2,4-dimethyl-1H-pyrrole-3-propanoic acid) is a new drug under investigation that inhibits receptor tyrosine kinases involved in tumor angiogenesis. In clinical pharmacokinetic studies, lower plasma concentrations of orally administered TSU-68 are observed after the second dose given within 12 h after the first dose. We examined the cause of this observation through in vivo and ex vivo approaches using rats in which a rapid decrease in the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
3
11
1
Order By: Relevance
“…This similarity makes the extrapolation of in vivo results between rats and humans more reliable. Furthermore, our group's previous work with rats demonstrated that decreased plasma concentrations of TSU-68 resulted from the autoinduction (Kitamura et al, 2007). Overall, therefore, the human in vitro results obtained in this study and the in vivo finding in rats strongly support the idea that the clinically observed decrease in the plasma concentrations of repeatedly administered TSU-68 is attributed to autoinduction via CYP1A1/2.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This similarity makes the extrapolation of in vivo results between rats and humans more reliable. Furthermore, our group's previous work with rats demonstrated that decreased plasma concentrations of TSU-68 resulted from the autoinduction (Kitamura et al, 2007). Overall, therefore, the human in vitro results obtained in this study and the in vivo finding in rats strongly support the idea that the clinically observed decrease in the plasma concentrations of repeatedly administered TSU-68 is attributed to autoinduction via CYP1A1/2.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, this decrease occurred as early as the second dose of TSU-68 on day 1. In preclinical studies, TSU-68 administered to rats was shown to induce hepatic P450 activity, which was responsible for its metabolism (autoinduction), thereby markedly decreasing plasma concentrations of TSU-68 within a day (Kitamura et al, 2007). However, this finding provides no conclusive evidence that the clinically observed decrease is due to this autoinduction, because there are interspecies differences in P450 induction (Kern et al, 1997;Lu and Li, 2001;Martignoni et al, 2006).…”
contrasting
confidence: 50%
“…Unlike several reported autoinduction cases where the induced P450 enzymes dominated the total clearance of the compounds in either human or preclinical species (Gibson et al, 2005;Shimizu et al, 2006;Kitamura et al, 2007), MK-0686 was eliminated via both hydrolytic reactions and CYP2C75-mediated oxidation in rhesus monkeys. The contribution of the former pathways seemed to be equal to or greater than the latter for the total clearance of MK-0686 (Fig.…”
Section: Downloaded Frommentioning
confidence: 91%
“…jpet.aspetjournals.org first two parameters is well precedented, tools for identifying important P450s are not readily available for preclinical species. Only limited efforts have been reported to investigate the P450 isozymes involved in autoinduction in dogs (Gibson et al, 2005) and rats (Kitamura et al, 2007). The remarkable reduction of systemic exposure of MK-0686 in rhesus monkeys after repeated oral administration presents the first report of autoinduction attributed to rhesus CYP2C75.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, other examples where induction of DMEs in rats is also observed in humans. For example, TSU-68, an experimental receptor tyrosine kinase inhibitor, showed autoinduction of CYP1A in rats (Kitamura et al 2007;Kitamura, Matsuoka et al 2008) and humans (Kitamura, Asanoma et al 2008;Sessa et al 2006).…”
Section: Animal Modelsmentioning
confidence: 99%